Retaining health carers: the role of personal and organisation job resources. Issue 2 (26th June 2019) - Almeida, Shamika; Fernando, Mario; Munoz, Albert; Cartwright, Susan
Abstract : Purpose: The purpose of this paper is to identify key personal and organisational resources that influence the engagement, well-being and job satisfaction of healthcare professionals working in Australia. Design/methodology/approach: Using the job demands–resources model, this study investigates how employee resources and organisation resources influence engagement, well-being and job satisfaction of health professionals in Australian hospitals. The authors collected survey data from a sample of healthcare professionals ( n =217) working in three hospitals in New South Wales, Australia. Findings: The results confirm the importance of the emotional health of employees on their well-being. The results concur with existing research that employees with higher levels of emotional health have more positive emotional and social interactions, and thus exhibit higher levels of well-being at work. The study also uncovers certain aspects of emotional health that can influence a range of employee outcomes. Practical implications: The findings link human resource management practices to unique motivators of healthcare professionals which, in turn, are likely to improve engagement, well-being and job satisfaction. Originality/value: The study highlights specific resources that support greater levels of well-being, engagement and job satisfaction in Australian hospitals.